OPTIMIZATION OF COMMUNITY ECONOMIC EMPOWERMENT THROUGH KELULUT BEE CULVITATION IN TANJUNG PASIR VILLAGE - Wahyu Ario Pratomo; Baktiar Bin Musa; Yasmin Chairunisa Muchtar; Yola Anggia; Walad Altsani (International Review of Practical Innovation, Technology and Green Energy (IRPITAGE), 2024)
Kelulut honey is one of the new commodities in Tanjung Pasir Village sub-district and is starting to be developed by the local community. The development of kelulut honey indirectly affects the income sector for the community and also has an impact on the development of tourism in the village. This study aims to identify and analyze the social capital used by the community in developing kelulut honey commodities. The research method used to conduct this study is a qualitative method that emphasizes the deepening of a meaning and phenomenon. The results of the study show that there is a use of social capital in efforts to develop kelulut honey as a community income sector and tourism sector. The social capital used includes: trust, networks and local community norms, so that the optimal use of social capital makes kelulut honey a commodity in Pantai Labu.